Analisis Hukum Islam dan Etika Terhadap Penggunaan Teknologi Deepfake oleh Remaja yang berimplikasi kepada Hukum dan Moral - Hadiyanto, Redi; Zahirah, Zalfa (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2025)
The development of deepfake technology that has been massively adopted by teenagers has caused serious problems because it has the potential to violate Islamic legal principles (such as the prohibition of al-kadhib and hifz al-‘irdh) and ethical norms. This study aims to analyze the use of deepfake by teenagers using the maqashid sharia theory, Kant's ethics, Kohlberg's moral theory, and Nonet-Selznick's responsive law, with qualitative normative-juridical methods and digital ethnography through literature studies, interviews with 15 scholars and 20 ethics-technology experts, and FGDs with 60 teenagers. The results show violations of Islamic principles, ethics (autonomy, non-maleficence, justice), and 12 articles of positive law with a 12-year criminal penalty, accompanied by moral impacts in the form of a crisis of trust and values, which demands Islamic value-based regulations and increased digital literacy.